Analisis Knuckle Arm Mobil Listrik Anobrain AR-1 dengan Metode Finite Element - Hafidz El Fariz; Kardiman; Boni Sena (Jurnal Serambi Engineering, 2024)
The aim of this research is to analyze the mechanical strength of knuckles, made from aluminum 6061 and alloy steel, using static analysis at maximum load. This maximum load is obtained from calculating the tire reaction load. Finally, this research uses the finite element method which produces results in Solidwork software to produce static analysis of the knuckle model. From the results of the simulation and analysis of the components, the level of displacement, stresses and safety factors will be known. The main reference for the results of this analysis is the safety factor. This research is used as a reference for the electric car team. The knuckle arm is very important so it must be paid attention to because damage to the knuckle arm affects the stability of the vehicle